Montaging Pushkin : Pushkin and visions of modernity in Russian twentieth-century poetry - Smith, Alexandra (Studies in Slavic literature and poetics, 2006)
Montaging Pushkin offers for the first time a coherent view of Pushkin's legacy to Russian twentieth-century poetry, giving many new insights. Pushkin is shown to be a Russian forerunner of Baudelaire. Furthermore it is argued that the rise of the Russian and European novel largely changed the ways Russian poets have looked at themselves and at poetic language; that novelisation of poetry is detectable in the major works of poetry that engaged in a creative dialogue with Pushkin, and that polyphonic lyric has been achieved. Alexandra Smith locates significant examples of Pushkin's cinematograp.